Guanylate cyclase-C as a therapeutic target in gastrointestinal disorders - Waldman, Scott A (Gut, 2018)
Functional gastrointestinal disorders (FGIDs) and IBDs are two of the most prevalent disorders of the GI tract and consume a significant proportion of healthcare resources. Recent studies have shown that membrane-bound guanylate cyclase-C (GC-C) receptors lining the GI tract may serve as novel therapeutic targets in the treatment of FGIDs and IBDs. GC-C receptor activation by its endogenous paracrine hormones uroguanylin and guanylin, and the resulting intracellular production of its downstream effector cyclic GMP, occurs in a pH-dependent manner and modulates key physiological functions. These include fluid and electrolyte homeostasis, maintenance of the intestinal barrier, anti-inflammatory activity and regulation of epithelial regeneration. Studies of the GC-C paracrine signalling axis have revealed the therapeutic potential of these receptors in treating GI disorders, including chronic idiopathic constipation and irritable bowel syndrome–constipation. This review focuses on the evolving understanding of GC-C function in health and disease, and strategies for translating these principles into new treatments for FGIDs and IBDs.